The Emergence of Student-Writers in Surakarta: Combating Religious Radicalism Among Youth in the Digital Age - Zaid Munawar; Muhammad Ishom (UIN Sunan Ampel Surabaya, 2023)
The rise of religious radicalism among young people in the Soloraya region has been greatly influenced by digital technology. Efforts to address this issue have emerged from student-writers in Surakarta. This research aims to examine the emergence of these student-writers in Surakarta, their responses to religious radicalism, the discussions on Islam within their community, and their methods of outreach in the digital era. Netnography was never applied to gather and examine data from online sources like websites and social media platforms. The findings reveal that student-writers started their involvement in 2017 through the establishment of the Center for the Study and Development of Islamic Boarding Schools (PKPPN) at IAIN Surakarta. Their discussions focus on unearthing the values of wisdom and Islamic moderation within the pesantren tradition, emphasizing principles like moderation, tolerance, equality, anti-violence, and patriotism. They have initiated the Literacy of Refined and Tolerant Islam (LISaN) program to promote a refined and tolerant form of Islam in daily life, both offline and online. This initiative aims to counteract the surge of religious radicalism among young people connected to the digital world.